Recent Advances in Electrical and Electronic Engineering and Computer Science Selected articles from ICCEE 2021, Malaysia - Zakaria, Zahriladha; Emamian, Seyed Sattar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book highlights recent research works on computer science, electrical and electronic engineering which was presented virtually during the 3rd International Conference on Computer Science, Electrical & Electronic Engineering (ICCEE 2021), August 2021. Written by leading researchers and industry professionals, the papers highlight recent advances and address current issues in the respective fields. .
Simulation of GSM Based Smart Energy Meter Presenting Electric Theft Detection and Prevention Mechanism by Using Arduino -- Model-Based Testing of Access Control Requirement in Multi-Tenant Application: An Extensive Life Cycle -- Survivable Biconnected Topology for Yemen s Optical Network -- A Study on Electric Field Distribution in Polymeric Insulator Using Finite Element Method -- Modelling and Simulation of Building-integrated Photovoltaics (BIPV) Installations in Swinburne University -- Ant Colony Optimization Algorithms for Routing in Wireless Sensor Networks: A Review -- Analyzing the Effects of Corona Ring Material & Dimensions on the Electric Field Distribution of 132kV Glass Insulator String using 2-D FEM -- Ultra-compact all-optical NAND Logic Gates Based on 4x4 MMI Coupler Using Silicon Hybrid Plasmonic Waveguides -- Microstrip Patch Antenna Arrays Design For 5G Wireless Backhaul Application At 3.5 GHz -- Transformer Life Estimation based on Degree of Polymerization with GUI -- Velocity-Based Control of Piston Trajectory in a Free-Piston Linear Electric Generator by Load Current Modulation -- GBI-based Wireless Home Automation System using IoT -- Embedded Machine Learning on a Programmable Neuromorphic Platform -- Investigation on Two Dimensional Photonic Crystal based all Optical Logic Gates -- Miniaturized Multiband Metamaterial Antenna For 5G Applications.
Keywords: Electrical engineering; Artificial intelligence; Quantum communication; Image processing -- Digital techniques; Computer vision; Electrical and Electronic Engineering; Artificial Intelligence; Quantum Communications and Cryptography; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer science -- Congresses; Electrical engineering -- Congresses